A Study of the Inclusion Complex Formed Between Cucurbit[8]uril and N,4-Di(pyridinyl)benzamide Derivative - Zhikang Wang; Mingjie Yang; Weibo Yang; Zhongzheng Gao; Hui Zhao; Gang Wei; Jifu Sun (Organics, 2025)
The interaction between cucurbit[8]uril (Q[8]) and the guest 1-methyl-4-(4-(1-methylpyridin-1-ium-4-yl)benzamido)pyridin-1-ium (PB2+) has been thoroughly investigated. Multiple techniques were employed, including 1H NMR spectroscopy, mass spectrometry, isothermal titration calorimetry (ITC), UV–vis absorption spectrophotometry, and quantum chemistry calculations. The experimental results and calculation analysis have clearly shown that in aqueous solution, the host Q[8] preferentially encapsulates the phenylpyridinium salt moiety of the PB2+ guest within its hydrophobic cavity, forming a 1:2 inclusion complex.